Report on currency and finance: Volume I Economic Review 1978-79 - Reserve Bank of India ([Bombay] Reserve Bank of India., 1978)
This volume considers as a whole, the developments in the economy during the year July 1978 to June 1979, discussed in details in the chapters that follow. The volume covers ten chapters. Chapter I, Review and Outlook. Chapter II, National Income, Savings and Investment. Chapter III, Agricultural and Industrial Output. Chapter IV, Price Trends and Price Policy. Chapter V, Monetary Developments. Chapter VI, Banking Developments. Chapter VII, Fiscal Developments. Chapter VIII, Industrial Finance. Chapter IX, Developments in Foreign Trade. Chapter X, Balance of Payments and International Monetary Developments.
Issues also carry theme title.
rpm 27/04/2018
Loans
Keywords: Finance; Currency question; Currency question; Finance; PUBLIC FINANCE; BANKS; BANKING; ECONOMIC CONDITIONS; INDIA; India